2021
DOI: 10.3390/su13020870
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Economic Complexity on the Formation of Environmental Culture

Abstract: This paper establishes economic complexity as a powerful predictor of environmental attitudes. While the economic complexity index (ECI) has been associated with a series of economic outcomes, yet there has not been a link in the literature between ECI and environmental attitudes. This research pushes forward the hypothesis that economic complexity shapes cultural values and beliefs. The research method used is a multilevel empirical analysis that associates aggregate values of the ECI, at the country level, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Ecological Footprint (EF) is a more comprehensive and major source of measurement of environmental damage, with greenhouse gas emissions first established by [35] and later improved by [36]. EF describes the social requirements of natural surroundings, as it gauges, by making additions of the natural accounting system, all means of natural resources required to support an economy.…”
Section: Environmental Degradationmentioning
confidence: 99%
“…Ecological Footprint (EF) is a more comprehensive and major source of measurement of environmental damage, with greenhouse gas emissions first established by [35] and later improved by [36]. EF describes the social requirements of natural surroundings, as it gauges, by making additions of the natural accounting system, all means of natural resources required to support an economy.…”
Section: Environmental Degradationmentioning
confidence: 99%
“…However, other studies (Saure and Zoabi, 2009) have revealed that economic complexity reduces female labour force participation. There are also studies where there is a U-shaped relationship between employment and economic complexity in the context of gender (Luci, 2009;Lapatinas et al, 2021). Contrary to these fi ndings, there are also studies showing that there is no concrete relationship between economic complexity and unemployment (Ferraz et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…This article makes two important contributions to the relevant literature. The fi rst contribution comes from the limited number of studies that analyse the impact of economic complexity on labour markets at the gender level (Goldin, 1990(Goldin, , 1991(Goldin, , 2000Black and Juhn, 2000;Barza et al, 2020;Saure and Zoabi, 2009;Luci, 2009;Lapatinas et al, 2021). These studies have examined the impact of economic complexity on employment, not the impact on unemployment.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of economic complexity to predict future growth has made its application relevant to topics in development economics ranging from income growth to the environment. Scholars have demonstrated that economic complexity contributes significantly to economic growth (Gala et al, 2016; Hausmann et al, 2013; Hidalgo & Hausmann, 2009; Sweet & Eterovic, 2019), income equality (Hartmann et al, 2017), export competitiveness (Olasehinde‐Williams & Oshodi, 2021), human development (Ferraz et al, 2018), jobs and employment (Adam et al, 2021) and better environmental performance (Boleti et al, 2021; Lapatinas et al, 2021; Neagu, 2019; Romero & Gramkow, 2021). However, the determinants of economic complexity are less frequently studied than its contributions (see, e.g., Bahar et al, 2022 for demographic determinants; Antonietti & Franco, 2021, Kamguia et al, 2022, Nguyen & Su, 2021 for financial determinants; and Sweet & Maggio, 2015 for institutional determinants).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of economic complexity to predict future growth has made its application relevant to topics in development economics ranging from income growth to the environment. Scholars have demonstrated that economic complexity contributes significantly to economic growth (Gala et al, 2016;Hausmann et al, 2013;Hidalgo & Hausmann, 2009;Sweet & Eterovic, 2019), income equality (Hartmann et al, 2017), export competitiveness (Olasehinde-Williams & Oshodi, 2021), human development (Ferraz et al, 2018), jobs and employment (Adam et al, 2021) and better environmental performance (Boleti et al, 2021;Lapatinas et al, 2021;Neagu, 2019;Romero & Gramkow, 2021).…”
mentioning
confidence: 99%